KONTRIBUSI MANAJEMEN PEMBIAYAAN DAN IKLIM MADRASAH TERHADAP PENINGKATAN MUTU PENDIDIKAN MADRASAH ALIYAH NEGERI DI ACEH UTARA - Nurmadiah, Nurmadiah (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2020)
This research is a descriptive quantitative study with an ex post facto design. The study population was 120 public madrasah aliyah teachers from each state madrasah aliyah in all districts of North Aceh. The research sample was selected from the population of curriculum representatives, student representatives, infrastructure representatives, public relations representatives and financial managers in 6 State Madrasah aliyah in North Aceh Regency. The hypothesis was analyzed with the help of SPSS 18 for windows at a significant level of 0.05. Based on the data analysis and hypothesis testing conducted, it is found that: there is a significant contribution between financial management towards improving the quality of madrasah, the results of this study are the value of Sig. amounting to 0,000. Therefore, the Sig. 0.000 <0.05, it can be said that the value of the WMS calculation which is in the very good category, there is a significant contribution between the madrasah climate and the improvement of the quality of the madrasah, in this study the Sig. amounting to 0,000. Therefore, the Sig. 0.000 <0.05, it can be said that it can be said that from the value obtained from the WMS calculation which is in a very good category and there is a significant contribution between financing management and madrasah climate significantly to improving the quality of madrasah, then the Sig. 0.021 <0.05, it can be said that there is a significant contribution between financial management and madrasah climate significantly to improving the quality of madrasah, thus it can be said that the research was successful.